In vivo Genome Editing Therapeutic Approaches for Neurological Disorders: Where Are We in the Translational Pipeline? - Lubroth, Pablo; Colasante, Gaia; Lignani, Gabriele (Frontiers in Neuroscience, 2021)
In vivo genome editing tools, such as those based on CRISPR, have been increasingly utilised in both basic and translational neuroscience research. There are currently nine in vivo non-CNS genome-editing therapies in clinical trials, and the pre-clinical pipeline of major biotechnology companies demonstrate that this number will continue to grow. Several biotechnology companies commercialising in vivo genome editing and modification technologies are developing therapies for CNS disorders with accompanying large partnering deals. In this perspective, the authors discuss the current genome editing and modification therapy pipeline and those in development to treat CNS disorders. The authors also discuss the technical and commercial limitations to translation of these same therapies and potential avenues to overcome these hurdles.